Strain sensor and flexible supercapacitor based on multifunctional hydrogel and preparation method and application of strain sensor and flexible supercapacitor
By regulating the content of BC, TA and LiCl in the hydrogel, combining the combination of P(AM-co-AA)/BC/TA/LiCl hydrogel and flexible conductive silver cloth, a high-sensitivity and fast-responsive strain sensor was prepared, and the durability of flexible supercapacitors was improved through VHB packaging, solving the problem of difficult balance of mechanical properties and insufficient water retention in traditional hydrogels in applications, achieving efficient strain sensing and flexible supercapacitor performance.
Patent Information
- Application Number
- CN202411797027.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In actual applications, traditional hydrogels have problems that they are difficult to balance the elongation of break and tensile strength, and their water retention, frost resistance and adhesion are insufficient, which limits their application prospects in the fields of flexible sensors and flexible supercapacitors.
By regulating the content of BC, TA and LiCl, the mechanical properties of the hydrogel are improved and the balance of elongation of break and tensile strength is achieved. The introduction of TA improves adhesion performance, LiCl enhances anti-freeze and water retention performance, combined with the combination of P(AM-co-AA)/BC/TA/LiCl hydrogel and flexible conductive silver cloth, a high-sensitivity and fast-responsive strain sensor was prepared, and the durability of flexible supercapacitors was improved through VHB package.
The high sensitivity and rapid response of the hydrogel strain sensor are achieved, the balance of elongation of break and tensile strength, and have excellent anti-freeze properties and long-term stability. Flexible supercapacitors exhibit good mechanical stability and electrochemical properties under tensile strain and low temperature environments.
Smart Images

Figure CN119700091A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of flexible wearable sensors, and in particular to a strain sensor and a flexible supercapacitor based on a multifunctional hydrogel, and a preparation method and application thereof. Background Art
[0002] Hydrogels have broad application prospects in the fields of flexible sensors and flexible supercapacitors due to their unique softness and biocompatibility. The mechanical properties of hydrogels are crucial to flexible sensors and flexible supercapacitors.
[0003] However, traditional hydrogels often have the problem of difficult balance between elongation at break and tensile strength, which limits their performance in practical applications. In addition, the water retention, antifreeze and adhesion of hydrogels are also key factors affecting their application effects. Therefore, it is urgent to develop a strain sensor and flexible supercapacitor based on multifunctional hydrogels and their preparation methods and applications. Summary of the invention
[0004] In view of this, the present application provides a strain sensor and flexible supercapacitor based on multifunctional hydrogel, and a preparation method and application thereof. By regulating the content of BC, TA and LiCl, the mechanical properties of the hydrogel are significantly improved, and the balance between the elongation at break and the tensile strength is achieved. The hydrogel strain sensor has the advantages of high sensitivity and fast response speed.
[0005] Specifically, the following technical solutions are included: In a first aspect, the present application provides a strain sensor based on a multifunctional hydrogel, the strain sensor comprising a P(AM-co-AA) / BC / TA / LiCl hydrogel and a flexible conductive silver cloth located at both ends of the P(AM-co-AA) / BC / TA / LiCl hydrogel; The P(AM-co-AA) / BC / TA / LiCl hydrogel has a three-dimensional porous structure and a continuously interconnected pore network, hydrogen bonds and topological interlocking are formed between the BC nanofibers and the P(AM-co-AA) polymer chains, and hydrogen bonds are formed between the TA and the P(AM-co-AA) polymer chains.
[0006] In a second aspect, the present application provides a method for preparing a strain sensor based on a multifunctional hydrogel, the preparation method comprising: (1) Preparation of P(AM-co-AA) / BC / TA / LiCl hydrogel: adding AM, AA, MBAA, APS, TA, and LiCl to an aqueous suspension of BC to obtain a first mixed solution; stirring the first mixed solution and then performing ultrasonic treatment to remove bubbles to obtain a second mixed solution; pouring the second mixed solution into a silicone mold, and performing a polymerization reaction under a first temperature environment to obtain a P(AM-co-AA) / BC / TA / LiCl hydrogel; (2) Flexible conductive silver cloth was fixed at both ends of the P(AM-co-AA) / BC / TA / LiCl hydrogel to obtain a strain sensor.
[0007] In some embodiments, the masses of AM, AA, MBAA, APS, TA, and LiCl are (1 g-3 g), (0.09 g-0.12 g), (0.1 mg-0.15 mg), (0.04 g-0.08 g), (0.001-0.04 g), and (0.001-0.8 g).
[0008] In some embodiments, the mass fraction of the aqueous suspension of BC is 0.001-0.2 wt %, the stirring time is 10 min-60 min, and the ultrasonic time is 1 min-15 min.
[0009] In some embodiments, the first temperature is 40° C.-80° C., and the polymerization reaction time is 60-180 min.
[0010] In a third aspect, the present application provides a flexible supercapacitor based on a multifunctional hydrogel, wherein the flexible supercapacitor comprises a CNTs / MnO2 flexible electrode, a P(AM-co-AA) / BC / TA / LiCl hydrogel and a CNTs / MnO2 collector, a first VHB encapsulation layer and a second VHB encapsulation layer, wherein the CNTs / MnO2 flexible electrode, the P(AM-co-AA) / BC / TA / LiCl hydrogel and the CNTs / MnO2 collector are sequentially laminated, and the laminated CNTs / MnO2 flexible electrode, the P(AM-co-AA) / BC / TA / LiCl hydrogel and the CNTs / MnO2 collector are encapsulated between the first VHB encapsulation layer and the second VHB encapsulation layer, and the flexible supercapacitor is a sandwich structure with symmetrical electrodes.
[0011] In a fourth aspect, the present application provides a method for preparing a flexible supercapacitor based on a multifunctional hydrogel, the preparation method comprising: (1) Immersing the elastic sponge substrate in a CNTs suspension, vacuum drying the substrate after immersion, and repeating the immersion and vacuum drying operations for multiple times to obtain a CNTs elastic sponge; (2) immersing the CNTs elastic sponge in a KMnO4 solution, and then drying the solution to obtain a CNTs / MnO2 elastic sponge; (3) Using a CNTs / MnO2 elastic sponge as an electrode of a flexible supercapacitor to obtain a CNTs / MnO2 flexible electrode; (4) Using a CNTs / MnO2 elastic sponge as the collector of a flexible supercapacitor to obtain a CNTs / MnO2 collector; (5) The first VHB encapsulation layer, the CNTs / MnO2 flexible electrode, the P(AM-co-AA) / BC / TA / LiCl hydrogel, the CNTs / MnO2 collector and the second VHB encapsulation layer are sequentially laminated to obtain a flexible supercapacitor.
[0012] In some embodiments, the soaking time in step (1) is 30 min-90 min, the soaking temperature is 20° C.-30° C., the vacuum drying time is 30 min-90 min, the vacuum drying temperature is 40° C.-80° C., and the mass fraction of the CNTs suspension is 10%-20%; In some embodiments, the soaking time in step (2) is 1 min-5 min, the soaking temperature is 50°C-80°C, the vacuum drying time is 1 h-5 h, the vacuum drying temperature is 60°C-100°C, and the mass fraction of KMnO4 solution is 0.1 mol / L-0.3 mol / L.
[0013] In a fifth aspect, the present application provides an application of a strain sensor based on a multifunctional hydrogel, wherein the strain sensor is used for human motion detection, detecting joint bending, blinking, frowning, smiling, chewing and lip reading signals.
[0014] The beneficial effects of the technical solution provided by this application include at least: (1) The present application provides a strain sensor based on a multifunctional hydrogel. Due to the introduction of P(AM-co-AA) / BC / TA / LiCl hydrogel, the cross-linking density is increased, thereby significantly improving the tensile properties of the hydrogel.
[0015] (2) The present application provides a method for preparing a strain sensor based on a multifunctional hydrogel. By regulating the content of BC, TA and LiCl, the mechanical properties of the hydrogel are significantly improved, achieving a balance between elongation at break (3208.3%) and tensile strength (303.3 kPa). The introduction of TA gives the hydrogel excellent adhesion properties, and adjustable adhesion strength can be achieved by regulating the content of TA. In addition, LiCl gives the hydrogel excellent antifreeze and water retention properties. The hydrogel strain sensor has the advantages of high sensitivity (maximum GF=6.93) and fast response speed.
[0016] (3) The present application provides a flexible supercapacitor based on a multifunctional hydrogel, using P(AM-co-AA) / BC / TA / LiCl hydrogel as the electrolyte, which can ensure that the flexible supercapacitor has good stretchability and flexibility. The double-layer encapsulation by VHB inhibits the water loss of the hydrogel electrolyte and improves the durability of the supercapacitor. In addition, the flexible and stretchable VHB material can retain the stretchability and flexibility of the main structure of the supercapacitor.
[0017] (4) This application provides a method for preparing a flexible supercapacitor based on a multifunctional hydrogel. The flexible supercapacitor prepared using a hydrogel electrolyte and a CNTs / MnO2 elastic sponge electrode exhibits excellent electrochemical performance at 0.5 mA / cm 2 At a current density of 133.6 mF / cm 2 The supercapacitor has an area capacitance of 73.1 mF / cm2 at -20°C and a capacitance retention rate of 87.1% after 3000 charge and discharge cycles. 2 The area capacitance of the material indicates its excellent mechanical stability and antifreeze performance.
[0018] (5) The present application provides an application of a strain sensor based on a multifunctional hydrogel, which can realize sensitive detection of human joint bending, muscle movement and lip reading of words. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0020] Figure 1 Schematic diagram of the structure of the P(AM-co-AA) / BC / TA / LiCl hydrogel of the present application; Figure 2 FTIR spectra of the P(AM-co-AA) hydrogel and P(AM-co-AA) / BC / TA hydrogel of the present application; Figure 3 is the SEM image of the P(AM-co-AA) / BC / TA hydrogel of the present application; Figure 4 (a) is the tensile curve of the P(AM-co-AA) / BC / TA hydrogel prepared by adding different contents of BC in this application; Figure 4 (b) shows the tensile strength of P(AM-co-AA) / BC / TA hydrogel prepared by adding different contents of BC in this application; Figure 4 (c) is the tensile curve of the P(AM-co-AA) / BC / TA hydrogel prepared by adding different contents of TA in this application; Figure 4 (d) is the tensile curve of the P(AM-co-AA) / BC / TA hydrogel prepared by adding different contents of LiCl in this application; Figure 5 (a) shows the PBTL in this application. 20 The hydrogel was subjected to 100 cycles of stretching (100%) curve; Figure 5(b) shows the PBTL in this application. 20 Continuous and progressive cyclic stretching (100~1000%) curve of hydrogel; Figure 6 (a) shows the PBTL in this application. 20 Schematic diagram of hydrogels tightly adhering to different substrate surfaces; Figure 6 (b) shows the PBTL in this application. 20 Schematic diagram of hydrogel tightly adhering to the surface of human skin; Figure 6 (c) shows the PBTL in this application. 20 Schematic diagram of lap shear tests of hydrogels with various substrates; Figure 7 (a) shows the PBTL0 hydrogel and PBTL in this application. 20 The effect diagram of the hydrogel's antifreeze test; Figure 7 (b) shows the PBTL0 hydrogel and PBTL 20 Hydrogel, PBTL 30 Hydrogel and PBTL 40 EIS curve of hydrogel at room temperature; Figure 7 (c) shows the PBTL0 hydrogel and PBTL 20 Hydrogel, PBTL 30 Hydrogel and PBTL 40 EIS curve of hydrogel at -20 °C; Figure 7 (d) shows the PBTL0 hydrogel and PBTL 20 Hydrogel, PBTL 30 Hydrogel and PBTL 40 Ionic conductivity of hydrogels at room temperature and -20 °C; Figure 8 For the PBTL0 hydrogel and PBTL in this application 20 Water loss curve test diagram of hydrogel at 50℃; Figure 9 (a) shows the PBTL in this application. 20Sensitivity curve of hydrogel strain sensor; Figure 9 (b) shows the PBTL in this application. 20 Response curve of hydrogel strain sensor; Figure 10 (a) shows the PBTL in this application. 20 Response of hydrogel strain sensors to small strains; Figure 10 (b) shows the PBTL in this application. 20 Response of hydrogel strain sensors to large strains; Figure 11 (a) shows the PBTL in this application. 20 Response of hydrogel strain sensor to step strain; Figure 11 (b) shows the PBTL in this application. 20 Response of hydrogel strain sensor to strain at different rates; Figure 11 (c) shows the PBTL in this application. 20 Long-term stability of hydrogel strain sensing; Fig.12 This is a schematic diagram of the structure of a flexible supercapacitor based on multifunctional hydrogel in this application; Fig.13 This is the SEM image of the flexible electrode of CNTs / MnO2 in this application; Fig.14 This is the EDS image of the flexible electrode of CNTs / MnO2 in this application; FIG15 (a) is a CV curve of a flexible supercapacitor based on a multifunctional hydrogel in the present application at different scan rates; FIG15 (b) is a GCD curve of the flexible supercapacitor based on multifunctional hydrogel in this application at different current densities; FIG15 (c) is an EIS curve of the flexible supercapacitor based on the multifunctional hydrogel in this application; FIG16 (a) is a CV curve of a flexible supercapacitor based on multifunctional hydrogel under different strains in this application; FIG16 (b) is a GCD curve of the flexible supercapacitor based on multifunctional hydrogel under different strains in this application; FIG16 (c) is the CV curve of the flexible supercapacitor based on the multifunctional hydrogel in this application at room temperature, 5°C and -20°C; FIG16 (d) is a GCD curve of the flexible supercapacitor based on the multifunctional hydrogel in this application at room temperature, 5°C and -20°C; Figure 17 (a) shows the response curve of the strain sensor based on the multifunctional hydrogel to the bending of the finger at different angles; Figure 17 (b) shows the response curve of the strain sensor based on the multifunctional hydrogel to different bending angles of the elbow; Figure 17 (c) shows the response curve of the strain sensor based on multifunctional hydrogel to walking and running; Figure 17 (d) shows the response curve of the strain sensor based on the multifunctional hydrogel to the finger tapping different letters; Figure 17 (e) is the response curve of the strain sensor based on the multifunctional hydrogel to blinking; Figure 17 (f) shows the response curve of the strain sensor based on the multifunctional hydrogel to chewing; FIG18 (a) is a schematic diagram of lip reading word detection based on a strain sensor of a multifunctional hydrogel; Figure 18 (b) shows the response curves of five strain sensors based on multifunctional hydrogels to lip reading “Hello”; Figure 18 (c) shows the response curves of five strain sensors based on multifunctional hydrogels to lip reading of “Thanks”; Figure 18 (d) shows the response curves of five multifunctional hydrogel-based strain sensors to lip reading of “Sorry”. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0022] In order to make the technical solutions and advantages of the present application more clear, the implementation methods of the present application will be further described in detail below with reference to the accompanying drawings.
[0023] In a first aspect, the present application provides a strain sensor based on a multifunctional hydrogel, the strain sensor comprising a P(AM-co-AA) / BC / TA / LiCl hydrogel and a flexible conductive silver cloth located at both ends of the P(AM-co-AA) / BC / TA / LiCl hydrogel. Figure 1 , the P(AM-co-AA) / BC / TA / LiCl hydrogel has a three-dimensional porous structure and a continuously interconnected pore network, hydrogen bonds and topological interlocking are formed between BC nanofibers and P(AM-co-AA) polymer chains, and hydrogen bonds are formed between TA and P(AM-co-AA) polymer chains.
[0024] Additional hydrogen bonds and topological interlocking were generated between BC nanofibers and P(AM-co-AA) polymer chains, which increased the crosslinking density of P(AM-co-AA) / BC / TA / LiCl hydrogel (hereinafter referred to as hydrogel) and strengthened the hydrogel network. TA can form hydrogen bonds with P(AM-co-AA) polymer chains, thus significantly improving the tensile properties of the hydrogel.
[0025] It should be noted that AM is acrylamide, AA is acrylic acid, BC is bacterial cellulose, TA is tannic acid, LiCl is lithium chloride, and P(AM-co-AA) / BC / TA / LiCl hydrogel is a composite material of polyacrylamide-acrylic acid, bacterial cellulose, tannic acid and lithium chloride.
[0026] In summary, the present application provides a strain sensor based on a multifunctional hydrogel. Due to the introduction of P(AM-co-AA) / BC / TA / LiCl hydrogel, the cross-linking density is increased, thereby significantly improving the tensile properties of the hydrogel.
[0027] In a second aspect, the present application provides a method for preparing a strain sensor based on a multifunctional hydrogel, the preparation method comprising: (1) Preparation of P(AM-co-AA) / BC / TA / LiCl hydrogel: AM, AA, MBAA, APS, TA, and LiCl were added to an aqueous suspension of BC to obtain a first mixed solution; the first mixed solution was stirred and then ultrasonically treated to remove bubbles to obtain a second mixed solution; the second mixed solution was poured into a silicone mold and polymerized under a first temperature environment to obtain P(AM-co-AA) / BC / TA / LiCl hydrogel.
[0028] In some embodiments, MBAA is N,N'-methylenebisacrylamide and APS is ammonium persulfate.
[0029] (2) Flexible conductive silver cloth was fixed at both ends of the P(AM-co-AA) / BC / TA / LiCl hydrogel to obtain a strain sensor.
[0030] In some embodiments, the masses of AM, AA, MBAA, APS, TA, and LiCl are (1 g-3 g), (0.09 g-0.12 g), (0.1 mg-0.15 mg), (0.04 g-0.08 g), (0.001-0.04 g), and (0.001-0.8 g).
[0031] In some embodiments, the mass fraction of the aqueous suspension of BC is 0.001-0.2 wt %, the stirring time is 10 min-60 min, and the ultrasonic time is 1 min-15 min.
[0032] In some embodiments, the first temperature is 40° C.-80° C., and the polymerization reaction time is 60-180 min.
[0033] In some embodiments, a one-pot method can be used to prepare P(AM-co-AA) / BC / TA / LiCl hydrogel. First, 2 g AM, 0.106 g AA, 0.136 mg MBAA, 0.06 g APS, 0.04 g TA, and 0.4 g LiCl were added to 7 g BC aqueous suspension (0.12 wt%). Then, the mixed solution was stirred for 0.5 h to fully mix all the components. The mixed solution was ultrasonically treated for 10 min to remove bubbles. Finally, the mixed solution was poured into a silicone mold and polymerized at 60 ° C for 2 h to obtain P(AM-co-AA) / BC / TA / LiCl hydrogel.
[0034] Figure 2 The FTIR spectra of P(AM-co-AA) hydrogel and P(AM-co-AA) / BC / TA / LiCl hydrogel prepared by the above method are shown. The FTIR spectrum of P(AM-co-AA) hydrogel shows the characteristic peak of hydrogel, 3337 cm -1 The peak at 1644 cm corresponds to the stretching vibration of NH -1 The peaks at 3312 cm and 3362 cm correspond to the C=O stretching vibration. The presence of these characteristic peaks indicates the successful polymerization of P(AM-co-AA) hydrogel. In the FTIR light of P(AM-co-AA) / BC / TA hydrogel, the two characteristic peaks move to 3312 cm -1 and 1623 cm -1 , which indicates that hydrogen bonds were formed among P(AM-co-AA), BC, and TA.
[0035] Figure 3 The microstructure of P(AM-co-AA) / BC / TA / LiCl hydrogel characterized by scanning electron microscopy is shown. P(AM-co-AA) / BC / TA / LiCl hydrogel has a three-dimensional porous structure and a continuously interconnected pore network, which provides channels for the transport of ions.
[0036] In some embodiments, the properties of P(AM-co-AA) / BC hydrogels with different BC contents (hereinafter referred to as PBx), P(AM-co-AA) / BC / TA hydrogels with different TA contents (hereinafter referred to as PBTy), and P(AM-co-AA) / BC / TA / LiCl hydrogels with different LiCl contents (hereinafter referred to as PBTLz) were tested, where x is the mass fraction of BC in the BC aqueous suspension, y is the mass of TA, and z is the mass ratio of LiCl to AM.
[0037] As shown in Figure 4 (a) and Figure 4 (b), the effect of BC content on the mechanical properties of P(AM-co-AA) / BC / TA / LiCl hydrogel was studied using a tensile test. As the mass fraction of BC in the BC suspension increased from 0 wt% to 0.08 wt%, the elongation at break and tensile strength of the hydrogel continued to increase. This is because additional hydrogen bonds and topological interlocking were generated between the BC nanofibers and the P(AM-co-AA) polymer chains, the crosslinking density of the hydrogel increased, and the hydrogel network was enhanced. As the BC content continued to increase, the elongation at break of the hydrogel gradually decreased. This is because excessive BC leads to excessive accumulation of crosslinked areas in the hydrogel, thereby reducing the distance between the chain segments, restricting the movement of the molecular chains, and resulting in a decrease in tensile properties. PB 0.12 The elongation at break and tensile strength of the hydrogel reached 1688.3% and 274.5 kPa, respectively, achieving a balance between the elongation at break and the tensile strength. Therefore, in order to avoid a catastrophic decrease in the tensile properties of the hydrogel after further increasing the BC content, a BC content of 0.12 wt% in the BC suspension can achieve better performance of the hydrogel.
[0038] In order to explore the effect of TA on the mechanical properties of hydrogels, P(AM-co-AA) / BC / TA / LiCl hydrogels with different TA contents were prepared and tensile tests were performed. As shown in Figure 4 (b), the tensile properties of the hydrogels increased with the addition of TA, among which PBT 0.04 The elongation at break reached 2416.1%. This is because TA can form hydrogen bonds with the P(AM-co-AA) polymer chains, thereby significantly improving the tensile properties of the hydrogel. However, as the TA content continued to increase, the tensile strength of the hydrogel gradually decreased, which was attributed to excessive cross-linking and uneven phase separation at high TA concentrations. Therefore, in order to avoid the continued deterioration of the tensile strength of the hydrogel due to excessive TA, a TA content of 0.04 g can make the hydrogel perform better.
[0039] In order to investigate the effect of LiCl on the mechanical properties of hydrogels, P(AM-co-AA) / BC / TA / LiCl hydrogels with different LiCl contents were prepared and tensile tests were performed. 20 The hydrogel has good mechanical properties, with an elongation at break of up to 3208.3% and a tensile strength of up to 303.3 kPa.
[0040] In some embodiments, the PBTL is tested by cyclic tension and cyclic compression tests. 20 Stability of the mechanical properties of the hydrogel. As shown in Figure 5 (a), the area of the PBTL20 hydrogel in the first cycle is much larger than that in the subsequent cycles, which is attributed to the "sacrificial network" effect of the BC nanofibers. The hydrogen bonds and topological interlocking between the BC nanofibers and the polymer network are sacrificial bonds in the hydrogel. These sacrificial bonds contribute to energy dissipation and can effectively protect the primary P(AM-co-AA) network in the hydrogel, thereby improving the mechanical behavior during stretching. In the following cyclic stretching, although the maximum stress decreased slightly compared to the first cycle, the hysteresis trajectory was almost the same, and the dissipated energy of each cycle did not deteriorate significantly. Therefore, BC nanofibers give the hydrogel good resistance to cyclic tensile fatigue. In addition, as shown in Figure 5 (b), the continuous progressive stretching test curves partially overlap, and the dissipated energy gradually increases with the increase of strain. This shows that the PBTL 20 Hydrogel has excellent self-recovery properties. The good resistance to cyclic tensile fatigue and self-recovery properties of hydrogel are very important for improving the stability of hydrogel flexible strain sensors.
[0041] In some embodiments, PBTL is tested 20 Adhesion properties of hydrogels. As shown in Figure 6(a), PBTL 20 The hydrogel can tightly adhere to the surfaces of various materials with different shapes, including steel, plastic, wood, PET, stone, rubber, silicone, fabric, and ceramics, which indicates that the hydrogel can be widely used in various substrates. As shown in Figure 6(b), PBTL 20 The hydrogel can adhere firmly to the finger joints and bend with the joints. The hydrogel can adhere to the fingers and will not fall off even when stretched. In order to quantitatively study PBTL 20 Adhesion strength of hydrogels to different substrates, PBTL 20 The hydrogel was subjected to lap shear tests with various substrates. The schematic diagram of the lap shear test is shown in Figure 6 (c).
[0042] In order to test the effect of TA content on the adhesion of hydrogels, PBTL with different TA contents were prepared. 20Hydrogel. As the TA content increases, the adhesion strength of the hydrogel to the wood gradually increases, indicating that the hydrogel has adjustable adhesion strength. The repeatability and durability of the adhesion performance are also crucial for practical applications. The excellent adhesion of the hydrogel is attributed to the TA in the hydrogel. The large amount of catechol groups on TA simulates the polyphenolic properties of mussel foot protein and can mimic the adhesion mechanism of mussels. Specifically, the catechol groups introduced by TA can quickly form multiple interactions with other groups on the surfaces of different substrates, thereby giving the hydrogel excellent adhesion.
[0043] In order to test the antifreeze and water retention properties of P(AM-co-AA) / BC / TA / LiCl hydrogel, PBTL0 and PBTL 20 The hydrogels were placed at -20 °C for 12 h, and then the tensile properties of the hydrogels were tested. As shown in Figure 7 (a), the PBTL0 hydrogel broke quickly, while the PBTL 20 The hydrogel still has excellent tensile properties, with a maximum elongation at break of 2589.5%. In addition to tensile properties, conductivity in low-temperature environments is also an important indicator for evaluating the antifreeze properties of hydrogels. LiCl provides abundant free ions, so the hydrogel has high ionic conductivity.
[0044] In order to quantitatively evaluate the ionic conductivity of the hydrogel, EIS measurements were performed on the hydrogel. As shown in Figures 7(b) and 7(c), the volume impedance of the hydrogel decreases with the increase of LiCl content. The volume impedance of the hydrogel shows the same trend at room temperature and -20°C, but the volume impedance increases significantly at -20°C. As shown in Figure 7(d), the ionic conductivity of the hydrogel increases with the increase of LiCl content. When the temperature drops to -20°C, the ionic conductivity of the hydrogel also decreases due to the decrease in ion diffusion rate, but still shows an ideal ionic conductivity (2.36 S / m). The excellent antifreeze performance of the hydrogel is attributed to the binding of LiCl to water molecules, which destroys the formation of hydrogen bonds between water molecules, thereby effectively inhibiting the formation of ice crystals.
[0045] Hydrogel materials usually have poor water retention capacity, which seriously limits their service life in practical applications. In order to test the water retention performance of hydrogels, hydrogels with different LiCl contents were placed in an oven at 50°C and their weights were recorded every 1 h. Figure 8 As shown in Figure 2, the water loss of PBTL0 hydrogel is extremely serious, while PBTL 20 The water retention performance of the hydrogel is greatly improved compared with that of the PBTL0 hydrogel. 20The mass retention rate of the hydrogel was 80.3%. The water retention performance of the hydrogel was attributed to LiCl. Specifically, the presence of LiCl strengthened the interaction with water molecules, reduced the proportion of free water in the hydrogel, increased the proportion of bound water, and thus reduced the evaporation of water.
[0046] PBTL 20 Hydrogels have good stretchability and ionic conductivity and are ideal for preparing flexible strain sensors. 20 The sensitivity curve of the hydrogel strain sensor is shown in Figure 9 (a). The GF gradually increases in the three strain ranges and reaches a maximum value of 6.93 in the strain range of 1631~3000%. As shown in Table 1-1, the maximum GF value and maximum detection range of the hydrogel strain sensor are better than some previously reported works. In addition, the hydrogel strain sensor exhibits a very fast response to external strain, and the response / recovery time under transient tensile deformation (50%) is 0.32 / 0.54 s, as shown in Figure 9 (b).
[0047] Table 1.1 Performance comparison of PBTL20 hydrogel strain sensor and reported hydrogel-based strain sensors Hydrogel materials Detection range Maximum GF Ca-GG / PAAm-ZP 0~500% 4.68 PAAm / CMC / LiCl 0~1200% 3.15 PEDOT:PSS-PVA 0~300% 4.07 PAM / SA / Sucrose / MXene 0~2617% 3.76 PAM / HPMC / MXene 0~1200 2.84 P(AM-co-AA) / BC / TA / LiCl (this application) 0~3000% 6.93 As shown in Figure 10 (a) and Figure 10 (b), the hydrogel strain sensor exhibits stable, fast and distinguishable electrical signal responses regardless of whether the dynamic tensile test is performed under small strains (1%, 3%, 6% and 10%) or large strains (100%, 200%, 300% and 400%), which indicates that the sensor has excellent strain resolution and repeatability. In addition, the hydrogel strain sensor exhibits a low detection limit of 1%, which indicates that the sensor has broad application potential in sensing subtle human movements.
[0048] The hydrogel strain sensor has excellent stability under step strain, and its ΔR / R0 value gradually increases with the increase of strain and remains stable under fixed strain, as shown in Figure 11 (a). In addition, due to the high resilience of the hydrogel, the ΔR / R0 value can return to the level at the initial strain without obvious drift, which shows the excellent reversibility and stability of the hydrogel strain sensor. As shown in Figure 11 (b), there is no obvious difference in the response of the sensor to 100% strain at different stretching speeds, which shows that the response of the hydrogel strain sensor is independent of the stretching speed and the ionic conductive path in the hydrogel is very stable. As shown in Figure 11 (c), the hydrogel strain sensor shows excellent long-term stability in 1000 stretching / releasing cycles under 100% strain, and there is no significant difference in the ΔR / R0 values of the sensors in the early and late stages of the cycle, which shows that the hydrogel strain sensor has excellent durability.
[0049] In summary, the present application provides a method for preparing a strain sensor based on a multifunctional hydrogel. By regulating the content of BC, TA and LiCl, the mechanical properties of the hydrogel are significantly improved, achieving a balance between elongation at break (3208.3%) and tensile strength (303.3 kPa). The introduction of TA gives the hydrogel excellent adhesion properties, and adjustable adhesion strength can be achieved by regulating the content of TA. In addition, LiCl gives the hydrogel excellent antifreeze and water retention properties. The hydrogel strain sensor has the advantages of high sensitivity (maximum GF=6.93) and fast response speed.
[0050] In a third aspect, the present application provides a flexible supercapacitor based on a multifunctional hydrogel (hereinafter referred to as a flexible supercapacitor), such as Fig.12 As shown, the flexible supercapacitor includes a CNTs / MnO2 flexible electrode, a P(AM-co-AA) / BC / TA / LiCl hydrogel and a CNTs / MnO2 collector, a first VHB encapsulation layer and a second VHB encapsulation layer. The CNTs / MnO2 flexible electrode, the P(AM-co-AA) / BC / TA / LiCl hydrogel and the CNTs / MnO2 collector are laminated in sequence. The laminated CNTs / MnO2 flexible electrode, the P(AM-co-AA) / BC / TA / LiCl hydrogel and the CNTs / MnO2 collector are encapsulated between the first VHB encapsulation layer and the second VHB encapsulation layer. The flexible supercapacitor has a sandwich structure with symmetrical electrodes.
[0051] In summary, the present application provides a flexible supercapacitor based on multifunctional hydrogel, with P(AM-co-AA) / BC / TA / LiCl hydrogel as electrolyte, which can ensure that the flexible supercapacitor has good stretchability and flexibility. Double-layer encapsulation by VHB inhibits water loss of the hydrogel electrolyte, improves the durability of the supercapacitor, and the flexible and stretchable VHB material can retain the stretchability and flexibility of the main structure of the supercapacitor.
[0052] In a fourth aspect, the present application provides a method for preparing a flexible supercapacitor based on a multifunctional hydrogel, the preparation method comprising: (1) Immersing the elastic sponge substrate in a CNTs suspension, vacuum drying the substrate after immersion, and repeating the immersion and vacuum drying operations for multiple times to obtain a CNTs elastic sponge; (2) soaking the CNTs elastic sponge in a KMnO4 solution, and then drying it to obtain a CNTs / MnO2 elastic sponge; (3) Using a CNTs / MnO2 elastic sponge as an electrode of a flexible supercapacitor to obtain a CNTs / MnO2 flexible electrode; (4) Using a CNTs / MnO2 elastic sponge as the collector of a flexible supercapacitor to obtain a CNTs / MnO2 collector; (5) The first VHB encapsulation layer, the CNTs / MnO2 flexible electrode, the P(AM-co-AA) / BC / TA / LiCl hydrogel, the CNTs / MnO2 collector and the second VHB encapsulation layer are sequentially laminated to obtain a flexible supercapacitor.
[0053] In some embodiments, the soaking time in step (1) is 30 min-90 min, the soaking temperature is 20° C.-30° C., the vacuum drying time is 30 min-90 min, the vacuum drying temperature is 40° C.-80° C., and the mass fraction of the CNTs suspension is 10%-20%; In some embodiments, the soaking time in step (2) is 1 min-5 min, the soaking temperature is 50°C-80°C, the vacuum drying time is 1 h-5 h, the vacuum drying temperature is 60°C-100°C, and the mass fraction of KMnO4 solution is 0.1 mol / L-0.3 mol / L.
[0054] In some embodiments, the specific preparation method can be to immerse the elastic sponge substrate in a CNTs suspension, vacuum dry at 60°C, and repeat the operation three times. Then, immerse the elastic sponge loaded with carbon nanotubes (CNTs) in a 0.1 mol / L KMnO4 solution at 70°C for 2 min. Finally, dry at 80°C for 3 h to obtain a CNTs / MnO2 flexible electrode. Then, the elastic sponge loaded with CNTs / MnO2 is used as a flexible electrode and collector, and the PBTL 20 The hydrogel was used as electrolyte to assemble a flexible supercapacitor with a sandwich structure and symmetrical electrodes. Finally, the supercapacitor was encapsulated using VHB tape.
[0055] In some embodiments, the elastic sponge loaded with carbon nanotubes (CNTs) is immersed in a 0.1 mol / L KMnO4 solution at 70°C for 2 min, and the reaction equation is:
[0056] The CNTs / MnO2 loaded flexible electrode was characterized by SEM. Fig.13 As shown in Figure 2, the electrode exhibits a porous structure. Fig.14 As shown, energy dispersive X-ray spectroscopy (EDS) shows that C, Mn, and O elements are evenly distributed on the electrode, indicating the presence of MnO2 and the uniform distribution of the electrode material.
[0057] The performance of flexible supercapacitors using CNTs / MnO2 electrodes at room temperature was tested. As shown in Figure 15 (a), the CV curve is approximately rectangular and symmetrical in the scan rate range of 5~100 mV / s. As shown in Figure 15 (b), the GCD curve of the supercapacitor at a current density of 0.5~2 mA / cm2 shows a linear profile and an isosceles triangle, indicating that typical reversible charge and discharge behavior occurs at the interface between the electrolyte and the electrode. As shown in Figure 15 (c), the electrochemical impedance spectroscopy shows that the internal resistance of the supercapacitor is 22.86 Ω, indicating that the supercapacitor has a low interface resistance and a fast and efficient kinetic process. According to the GCD curves at different current densities, the area capacitance can be calculated, and the supercapacitor has good cycle stability and durability.
[0058] The mechanical reliability of the supercapacitor was evaluated by measuring the CV curve and GCD curve under different tensile strains. As shown in Figure 16 (a) and Figure 16 (b), as the tensile strain increases, the CV and GCD curves deviate slightly from the original curves and do not deteriorate significantly. The results show that stretching has no significant effect on the electrochemical properties of the supercapacitor, and the supercapacitor has excellent mechanical reliability. In order to explore the antifreeze properties of the supercapacitor, the assembled supercapacitor was placed at 5°C and -20°C for 12 h, and its CV curve and GCD curve were measured. As shown in Figure 16 (c) and Figure 16 (d), the CV curves at 5°C and -20°C deviate from the initial shape, the voltage drop of the GCD curve increases, and the charge and discharge time decreases. The GCD curve at low temperature still remains approximately triangular, and still maintains 73.1 mF / cm at -20°C. 2 The area capacitance of the supercapacitor is 2.5×10-1.5 W, which indicates that the supercapacitor has excellent antifreeze performance.
[0059] In summary, the present application provides a method for preparing a flexible supercapacitor based on a multifunctional hydrogel. The flexible supercapacitor prepared using a hydrogel electrolyte and a CNTs / MnO2 elastic sponge electrode exhibits excellent electrochemical performance at 0.5 mA / cm 2 At a current density of 133.6 mF / cm 2 The area capacitance of the supercapacitor was 73.1 mF / cm2 at -20°C and the capacitance retention rate was 87.1% after 3000 charge and discharge cycles. 2 The area capacitance of the material indicates its excellent mechanical stability and antifreeze performance.
[0060] In a fifth aspect, the present application provides an application of a strain sensor based on a multifunctional hydrogel, and the strain sensor is used for human motion detection, detecting joint bending, blinking, frowning, smiling, chewing and lip reading signals.
[0061] Based on the advantages of the above-mentioned multifunctional hydrogel-based strain sensor (hereinafter referred to as hydrogel sensor), it can be used as a wearable sensor to monitor the vigorous and fine movements of the human body. As shown in Figure 17 (a), the hydrogel sensor is attached to the finger joint, and the hydrogel sensor ΔR / R0 changes with the bending angle of the finger from 30 o Increased to 120 oThe hydrogel strain sensor increases in a step-like manner and returns to the initial value when the finger returns to its original state. Similarly, the hydrogel strain sensor can detect the elbow and leg movements of volunteers. As shown in Figure 17 (b), when detecting elbow bending at different angles, the ΔR / R0 value increases with the increase of the elbow bending angle and shows a repeatable response under multiple bending and release cycles. In addition, the hydrogel sensor is fixed on the knee joint for detecting walking and running. The hydrogel sensor produces a clearly distinguishable response to movements of different frequencies, as shown in Figure 17 (c). The hydrogel sensor is fixed on the index finger joint to record the change in the ΔR / R0 value of the hydrogel sensor when typing on the keyboard. As shown in Figure 17 (d), the hydrogel sensor responds quickly to the typing of different letters "A", "UPC" and "Sensor" and produces different characteristic signals, which shows that the hydrogel sensor is able to detect small movements of the joints. The hydrogel sensor can detect not only human joint movements, but also human muscle movements. The hydrogel sensor is fixed on the brow and masseter muscles of the volunteers to monitor small muscle movements close to the skin. As shown in Figures 17(e) and 17(f), the hydrogel sensor produced sensitive responses to blinking and chewing.
[0062] In view of the excellent detection ability of hydrogel sensors for tiny muscle movements, an arc array of 5 hydrogel sensor units is distributed on the muscles around the lips to detect the tiny movements of the muscles around the lips when lip-reading different words, as shown in Figure 18 (a). As shown in Figures 18 (b), 18 (c) and 18 (d), the 5 hydrogel sensing units can accurately detect the characteristic waveforms of the lip-reading of the three words "Hello", "Thanks" and "Sorry", which shows that hydrogel sensors can be used to extract lip-reading information and have important application potential in helping aphasia patients communicate.
[0063] In summary, the present application provides an application of a strain sensor based on a multifunctional hydrogel, which can realize sensitive detection of human joint bending, muscle movement and lip reading of words.
[0064] In the present application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance. The term "plurality" refers to two or more than two, unless otherwise clearly defined.
[0065] Those skilled in the art will readily appreciate other embodiments of the present application after considering the specification and practicing the present application disclosed herein. The present application is intended to cover any variations, uses or adaptations of the present application, which follow the general principles of the present application and include common knowledge or customary techniques in the art that are not disclosed in the present application. The specification and examples are intended to be exemplary only.
[0066] It should be understood that the present application is not limited to the precise structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present application is limited only by the appended claims.
Claims
1. A strain sensor based on multifunctional hydrogel, characterized in that: The strain sensor includes a P(AM-co-AA) / BC / TA / LiCl hydrogel and a flexible conductive silver cloth located at both ends of the P(AM-co-AA) / BC / TA / LiCl hydrogel; The P(AM-co-AA) / BC / TA / LiCl hydrogel has a three-dimensional porous structure and a continuously interconnected pore network, hydrogen bonds and topological interlocking are formed between the BC nanofibers and the P(AM-co-AA) polymer chains, and hydrogen bonds are formed between the TA and the P(AM-co-AA) polymer chains.
2. A method for preparing a strain sensor based on a multifunctional hydrogel, characterized in that: The preparation method comprises: (1) Preparation of P(AM-co-AA) / BC / TA / LiCl hydrogel: adding AM, AA, MBAA, APS, TA, and LiCl to an aqueous suspension of BC to obtain a first mixed solution; stirring the first mixed solution and then performing ultrasonic treatment to remove bubbles to obtain a second mixed solution; pouring the second mixed solution into a silicone mold, and performing a polymerization reaction under a first temperature environment to obtain a P(AM-co-AA) / BC / TA / LiCl hydrogel; (2) Flexible conductive silver cloth was fixed at both ends of the P(AM-co-AA) / BC / TA / LiCl hydrogel to obtain a strain sensor.
3. The method for preparing a strain sensor based on a multifunctional hydrogel according to claim 2, characterized in that: The masses of AM, AA, MBAA, APS, TA, and LiCl are (1g-3g), (0.09g-0.12g), (0.1mg-0.15mg), (0.04g-0.08g), (0.001-0.04g), and (0.001-0.8g).
4. The method for preparing a strain sensor based on a multifunctional hydrogel according to claim 2, characterized in that: The mass fraction of BC aqueous suspension is 0.001-0.2 wt%, the stirring time is 10 min-60 min, and the ultrasonic time is 1 min-15 min.
5. The method for preparing a strain sensor based on a multifunctional hydrogel according to claim 2, characterized in that: The first temperature is 40°C-80°C, and the polymerization reaction time is 60-180 minutes.
6. A flexible supercapacitor based on multifunctional hydrogel, characterized in that: The flexible supercapacitor includes a CNTs / MnO2 flexible electrode, a P(AM-co-AA) / BC / TA / LiCl hydrogel and a CNTs / MnO2 collector, a first VHB encapsulation layer and a second VHB encapsulation layer. The CNTs / MnO2 flexible electrode, the P(AM-co-AA) / BC / TA / LiCl hydrogel and the CNTs / MnO2 collector are laminated in sequence. The laminated CNTs / MnO2 flexible electrode, the P(AM-co-AA) / BC / TA / LiCl hydrogel and the CNTs / MnO2 collector are encapsulated between the first VHB encapsulation layer and the second VHB encapsulation layer. The flexible supercapacitor is a sandwich structure with symmetrical electrodes.
7. A method for preparing a flexible supercapacitor based on multifunctional hydrogel, characterized in that: The preparation method comprises: (1) Immersing the elastic sponge substrate in a CNTs suspension, vacuum drying the substrate after immersion, and repeating the immersion and vacuum drying operations for multiple times to obtain a CNTs elastic sponge; (2) immersing the CNTs elastic sponge in a KMnO4 solution, and then drying the solution to obtain a CNTs / MnO2 elastic sponge; (3) Using a CNTs / MnO2 elastic sponge as an electrode of a flexible supercapacitor to obtain a CNTs / MnO2 flexible electrode; (4) Using a CNTs / MnO2 elastic sponge as the collector of a flexible supercapacitor to obtain a CNTs / MnO2 collector; (5) The first VHB encapsulation layer, the CNTs / MnO2 flexible electrode, the P(AM-co-AA) / BC / TA / LiCl hydrogel, the CNTs / MnO2 collector and the second VHB encapsulation layer are sequentially laminated to obtain a flexible supercapacitor.
8. The method for preparing a flexible supercapacitor based on a multifunctional hydrogel according to claim 7, characterized in that: The soaking time in step (1) is 30 min-90 min, the soaking temperature is 20° C.-30° C., the vacuum drying time is 30 min-90 min, the vacuum drying temperature is 40° C.-80° C., and the mass fraction of the CNTs suspension is 10%-20%.
9. The method for preparing a flexible supercapacitor based on a multifunctional hydrogel according to claim 7, characterized in that: The soaking time in step (2) is 1 min-5 min, the soaking temperature is 50° C.-80° C., the vacuum drying time is 1 h-5 h, the vacuum drying temperature is 60° C.-100° C., and the mass fraction of the KMnO4 solution is 0.1 mol / L-0.3 mol / L.
10. An application of a strain sensor based on a multifunctional hydrogel, characterized in that: The strain sensor is used for human motion detection, detecting joint bending, blinking, frowning, smiling, chewing and lip reading signals.
Citation Information
Patent Citations
Preparation method of flexible strain sensor based on nanocellulose-carbon nanotube / polyacrylamide conductive hydrogel
CN110183688A
Preparation method of anti-freezing organic-hydrogel with reversible adhesion and self-healing properties
CN111333872A
Multifunctional ionized water gel, strain sensor, flexible all-solid-state supercapacitor, and preparation methods and applications of multifunctional ionized water gel, strain sensor and flexible all-solid-state supercapacitor
CN116333379A
Adhesive self-healing organic hydrogel sensor and preparation method thereof
CN116655954A
Antibacterial self-healing composite dual-network hydrogel as well as preparation method and application thereof
CN116751432A
Cited By
Anti-swelling high-adhesion hydrogel strain sensor for underwater monitoring and preparation method thereof
CN120445023A
Anti-swelling, highly adhesive hydrogel strain sensor for underwater monitoring and its preparation method
CN120445023B
Multifunctional flexible sensor
CN121230923A